Investigating the association between iron and lipid metabolism with relevance to non-alcoholic fatty liver disease - Kidman, Clinton James (Curtin University, 2022)
Liver iron accumulation is associated with metabolic conditions such as non-alcoholic fatty liver disease and has been shown to impair health outcomes. This study utilised a combination of traditional molecular biology paired with synchrotron multimodal imaging and revealed iron accumulation is a wolf in sheep’s clothing, with an initially positive effect of reducing liver fat. However, it appears to radicalise poly-unsaturated fat leading to mitochondrial and peroxisomal dysregulation, furthering liver damage.